DESIGN AND ANALYSIS OF ROLLER SCREW MECHANISM FOR AN ELECTRIC CYLINDER (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Electric cylinder is a device which consists of an electric motor, roller screw mechanism, belt and pulley assembly, sub rollers. Electric cylinder is having a good control over nonlinear properties like motion and position control. Roller screw mechanism consists of assembly of main roller and sub roller which is driven by an electric motor for having control over the nonlinear properties. The paper mainly consists of design of a roller screw mechanism of an electric cylinder for a hand lever operated plastic injection moulding machine. The analysis of roller screw mechanism is done by using the ANSYS 16.2 software.